Preliminary classification of mechanical transmissions with gearing by means of the third element and motionless axes; Ресурсоэффективным технологиям - энергию и энтузиазм молодых - Ivkina O. P. (Modern issues of science and technologies, 2015)
Заглавие с титульного экрана